The emphasis of student test scores in teacher appraisal systems - Smith, William C.; Kubacka, Katarzyna (Education Policy Analysis Archives, 2017)
Over the past 30 years teachers have been held increasingly accountable for the quality of education in their classroom. During this transition, the line between teacher appraisals, traditionally an instrument for continuous formative teacher feedback, and summative teacher evaluations has blurred. Student test scores, as an ‘objective’ measure, are increasingly used in teacher appraisals in response to historic questions that evaluations are based on ‘subjective’ components. Their central position in appraisals is part of a larger Global Testing Culture, where standardized tests are linked with high stakes outcomes. Although most teacher appraisal systems are based on multiple components, the prominence of testing as the taken for granted measure of quality suggests that not all components are given equal weight or seen as equally important. This article further explores the role of testing in high stakes teacher appraisal systems across 33 countries using data from the 2013 TALIS; addressing both the prominence of student test scores and their relative importance in teacher’s perceived feedback utility. Results indicate that, while rarely applied in isolation, student test scores are the most common component used in teacher appraisals. Relative to other components, student achievement is more often emphasized and, when emphasized in feedback, teachers are more likely to feel their appraisal had limited impact on their instruction and was completed solely as an administrative exercise.